Reachable station - Muhamad Pozi, Muhammad Asyrafi; Zainodin, Nurul Wahidah Umairah; Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2017)
Reachable station enable users or patrons to access the library materials and such thing on the specific shelves based on the tablet provided. Thus, it is also have two signs (green and red lamp) to indicate the library materials that they looking for whether it can be accessible or not. After that, they will scan the barcode of the library materials and can borrowing the books on that time. Therefore, each shelf has their own security alarm which means here, when they locate the wrong book on the shelf it would make a “beep” sound. Each library materials have their own security tag details for scanning into the tablet and to breakable the security tag during checkout of borrowing the books on the shelf from tablet. The users and patrons will know the availability of the library materials itself on the specific shelves according to tablets given located in front of shelves based on the subject given. Then, they also can know the details of the library materials that they want to know/ borrowed regarding to the specific shelf on the tablet. More interestingly, each library materials have their own security tag that to be located at the right shelves based on the subject.